The Effects of Macroeconomic and Bank Specific Factors on Nonperforming Financing in Sharia Commercial Bank in Indonesia - Keti Purnamasari; Tariza Putri Ramayanti (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2019)
Financing risk is often associated with the risk of default. This risk refers to the potential losses faced by the bank when financing provided to debtors is stuck. The purpose of this paper is to analyze the effect of macroeconomic and bank specific factors on nonperforming financing in sharia commercial bank in Indonesia. The macroeconomic factors included; inflation and Bank Indonesia Certificates Sharia (SBIS). The Bank specific factors included; Capital Adequacy Ratio (CAR), Return on Assets (ROA), Operations Expenses to Operations Income (BOPO), and Financing to Deposit Ratio (FDR). The period covered under this study was January 2011 to December 2017. Data was collected from Bank Indonesia website and Indonesia Banking Statistics. Contrary to other studies, the inflation and SBIS have not been found statistically significant with nonperforming financing. The results also show that NPF can be explained mainly by Bank specific factors. CAR, ROA, and FDR have a negative effect on NPF while BOPO has a positive effect on NPF.